2015
DOI: 10.1210/jc.2014-3469
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Markers of Insulin Sensitivity and Insulin Secretion Are Associated With Spontaneous Postnatal Growth and Response to Growth Hormone Treatment in Short SGA Children: the North European SGA Study (NESGAS)

Abstract: Genetic allele scores indicative of insulin sensitivity and insulin secretion were associated with spontaneous postnatal growth and responses to GH therapy in short SGA children. Further pharmacogenetic studies may support the rationale for adjuvant therapies by informing the mechanisms of treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Prenatal starvation is associated with epigenetic changes that could persist throughout life, causing a tendency for energy conservation and thus overweight [36, 37]. Children with catch-up growth postnatally have better insulin sensitivity than other children, so these children will have a favorable linear growth and weight development [38]. However, most children born small for gestational age catch up in weight and length before 12 months of age [25], but this was not the case in our study subjects who experienced catch-up at a later age.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal starvation is associated with epigenetic changes that could persist throughout life, causing a tendency for energy conservation and thus overweight [36, 37]. Children with catch-up growth postnatally have better insulin sensitivity than other children, so these children will have a favorable linear growth and weight development [38]. However, most children born small for gestational age catch up in weight and length before 12 months of age [25], but this was not the case in our study subjects who experienced catch-up at a later age.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lower insulin sensitivity and insulin secretion are associated with reduced responses to GH treatment in SGA children(8,9). We recently employed a Mendelian randomisation approach to illustrate the likely causal link between insulin resistance and GH sensitivity in short SGA children: multiallele scores indicative of insulin resistance were associated with lower IGF-1 and height responses to GH treatment(10). In adults, the same multiallele score is associated with a lesser body fat, particularly in the gluteofemoral region and limbs(11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we and others have shown that children born small for gestational age (SGA) who had higher IGF-I concentrations had a lower insulin sensitivity and a poor growth response to rhGH treatment (40,41). To confirm this association, we used the Mendelian randomization approach in a group of SGA children and found an independent association between alleles coding for insulin sensitivity and first year height velocity and IGF-I responses to rhGH suggesting a causal link between insulin sensitivity and IGF-I (42). Metabolic markers may be part of the causal pathway in the relation between IGF-I and diabetes, but it is also possible that IGF-I is truly confounded by obesity because obesity has a major blunting effect on the GH secretion, whereas circulating IGF-I levels will stay unaffected (43).…”
Section: Discussionmentioning
confidence: 90%